Simulación de la subestación José María Moral, cantón Pujilí de la provincia de Cotopaxi, para determinar la cargabilidad del transformador - Galarza Jaya, Marco Orlando (2016)
In Ecuador, the increase in the demand of electrical energy is constant, because the electricity is used in the urban and rural areas and this is the reason why it is considered like a basic service. For that increase in demand that so new electric stations are created continually, so the project of transmission, subtransmission, electricity energy distribution and transformers should be manages together. The transformers are, maybe, the most important electrical machine and should be emphasis in the developing of a demand projection study for reasons such as the economic, quality, availability and the reliability. In the following example was performed a chargeability analysis to determine the current status of the substation José María Morán from Pujilí canton in Cotopaxi Province.